Nebula : Fondazione in between Art Film - Stoppani, Bianca; Rabottini, Alessandro; Bigazzi, Leonardo (Venice : Marsilio Arte s.r.l., 2024)
Mahmoud, Basir ; Meyers, Ari Benjamin ; Nyampeta, Christian ; Calò, Giorgio Andreotta ; Abbas, Basel ; Abou-Rahme, Ruanne ; Marchelle, Cinthia ; Mata Machado, Tiago ; Ismailova, Saodat ; Marcon, Diego
Nebula, Complesso dell'Ospedaletto, Venice, April 17 - November, 2024
boek